Effects of tetrahydrocannabinol on balance and gait in patients with dementia: A randomised controlled crossover trial. (February 2017) - van den Elsen, Geke AH; Tobben, Lieke; Ahmed, Amir IA; Verkes, Robbert Jan; Kramers, Cornelis; Marijnissen, Radboud M; Olde Rikkert, Marcel GM; van der Marck, Marjolein A
Oral tetrahydrocannabinol (THC) is currently studied for its possible efficacy on dementia-related neuropsychiatric symptoms (NPS), but might lead to increased risk of falling. This was a randomised, double-blind, crossover study to evaluate the effects of THC on mobility in dementia patients. Eighteen community-dwelling patients ( M age =77 years) received 1.5 mg of oral THC twice daily and placebo, in random order, for three days, separated by a four-day washout. Balance and gait were assessed using SwayStar TM and GAITRite TM within two hours after administration, in two consecutive intervention periods, under the following conditions: standing with eyes open (EO) and eyes closed (EC), preferred speed walking with and without a cognitive dual task. THC significantly increased sway during standing EC (roll angle 0.32[±0.6]°, p =0.05; pitch angle 1.04[±1.5]°, p =0.009; pitch velocity 1.96[±3.3]°/s, p =0.02), but not during standing EO. During preferred speed walking, THC increased stride length (4.3[±5.4] cm, p =0.005) and trunk sway (pitch angle 1.18[±1.6]°, p =0.005). No effects were observed during dual task walking. No differences in the number and type of adverse events were found, and no falls occurred after administration of THC. This study showed that 3 mg of THC per day has a benign adverse event profile regarding mobility and was well tolerated by community-dwelling dementia patients.